1991
DOI: 10.1016/0378-1135(91)90039-i
|View full text |Cite
|
Sign up to set email alerts
|

The use of enzyme-linked immunosorbent assay systems for serology and antigen detection in parvovirus, coronavirus and rotavirus infections in dogs in The Netherlands

Abstract: Complex trapping blocking (CTB) enzyme-linked immunosorbent assays (ELISAs) and indirect ELISAs for the detection of antibodies to canine parvovirus (CPV), canine coronavirus (CCV) and rotavirus in sera of dogs were established. Double antibody sandwich ELISAs for the detection of CPV-, CCV- and rotavirus antigens in fecal samples were also developed. Both the serological and antigen-detection ELISAs were used to screen samples from dogs in The Netherlands, with or without a history of acute diarrhea. It was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 19 publications
(20 reference statements)
3
25
0
2
Order By: Relevance
“…Both viruses were isolated from all feces samples collected. Earlier serological and virological studies had demonstrated that puppies and dogs from kennels and animal shelters are particularly exposed to these infections (Rimmelzwaan et al, 1991;Tennant et al, 1993;Bandai et al, 1999;Naylor et al, 2001;Yesilbag et al, 2004;Schulz et al, 2008). The high prevalence observed here reflects the high contagiosity of these two viruses.…”
Section: Discussionsupporting
confidence: 47%
“…Both viruses were isolated from all feces samples collected. Earlier serological and virological studies had demonstrated that puppies and dogs from kennels and animal shelters are particularly exposed to these infections (Rimmelzwaan et al, 1991;Tennant et al, 1993;Bandai et al, 1999;Naylor et al, 2001;Yesilbag et al, 2004;Schulz et al, 2008). The high prevalence observed here reflects the high contagiosity of these two viruses.…”
Section: Discussionsupporting
confidence: 47%
“…Since then, several CCoV outbreaks have been reported worldwide, showing that CCoV is an important enteropathogen of the dog. Serological and virological investigations have demonstrated that CCoV is widespread in dog population, mainly in kennels and animal shelters (Carmichael, 1978;Rimmelzwaan et al, 1991;Tennant et al, 1993;Möstl et al, 1994;Bandai et al, 1999;Naylor et al, 2001b;Yeşilbag et al, 2004;Schulz et al, 2008). CCoV infection is characterised by high morbidity and low mortality, as well as by a typical faecal-oral route of transmission (Tennant et al, 1991).…”
Section: History and Pathobiologymentioning
confidence: 99%
“…Assessment of antibodies by the virus neutralisation assay (Mochizuki et al, 1987), or by indirect enzyme-linked immunosorbent assay (ELISA) (Rimmelzwaan et al, 1991;Tuchiya et al, 1991) provides an indication of the exposure of an animal to CCoV. Detection of immunoglobulin M (IgM) and IgG against CCoV by indirect ELISA (Tennant et al, 1991;Naylor et al, 2001) determines current or previous exposure of an animal to CCoV.…”
Section: Introductionmentioning
confidence: 99%